Effects of Dietary Corn Dried Distillers Grains with Solubles Withdrawal on Finishing Pig Performance and Carcass Characteristics - A. B. Lerner; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; R. D. Goodband; C. Hastad; K. Coble; E. Arkfeld; H. C. Cartagena; C. Vahl (Kansas Agricultural Experiment Station Research Reports, 2018)
Two experiments were conducted to evaluate the effects of removing corn dried distillers grains with solubles (DDGS) at increasing intervals before harvest on finishing pig performance and carcass characteristics. For Exp. 1, 985 finishing pigs [initially 219 ± 5.5 lb body weight (BW)] were used in a 28-d growth study. There were 12 pens per treatment with 19 to 21 pigs per pen. There were four treatments decreasing in duration of withdrawal of DDGS from diets before final marketing: 28, 21, 14, or 0 d withdrawal. Regardless of treatment, pens of pigs were topped according to a typical summer marketing strategy with one top prior to final barn dump. All pens were topped by removing the 17% heaviest pigs on d -21 resulting in a final barn dump of approximately 83% of starting barn inventory. Overall, there was no evidence for effects of DDGS withdrawal time on final BW, average daily feed intake (ADFI), or feed efficiency (F/G;P>0.111); however, as withdrawal time increased, average daily gain (ADG) linearly increased (P= 0.022) and iodine value decreased (linear,P= 0.001). There was no evidence for treatment differences for hot carcass weight (HCW) or loin depth (P>0.106); however, dressing percentage was linearly increased (P= 0.001) with increased withdrawal time. Backfat depth was also decreased (quadratic;P= 0.019) and percentage lean increased (quadratic;P= 0.033) as DDGS withdrawal time increased. Feed cost and gain value were increased (linear,P<0.020) resulting in a marginally significant (P<0.100) increase in income over feed cost (IOFC) with increased withdrawal duration. In Exp. 2, 1,158 finishing pigs (initially 232 ± 4.3 lb BW) were used in a 35-d growth study. There were 15 pens per treatment with 17 to 21 pigs per pen. Similar to the first experiment, there were four treatments decreasing in duration of withdrawal of DDGS from diets before final marketing: 35, 28, 14, or 0 d withdrawal. All pens were topped according to a typical winter marketing strategy with two marketing events prior to the final barn dump. All pens were marketed by removing the 15% heaviest pigs on d -28, the 28% heaviest pigs on d -14, and a final barn dump of approximately 57% of starting barn inventory. There was no evidence that final BW, overall ADG, or overall F/G differed across treatments with increasing DDGS withdrawal times (P>0.116). Overall average daily feed intake increased (linear,P= 0.015) as time withdrawn from DDGS before final marketing increased. Iodine value decreased (P<0.022) and dressing percentage increased (linear;P= 0.034) with increasing withdrawal time. Lastly, feed cost and feed cost per lb of gain increased (linear,P<0.003) with increasing DDGS withdrawal time. In conclusion, these experiments demonstrate that longer feeding duration of DDGS before harvest decreases carcass yield and increases iodine value. Feed cost is reduced with longer feeding of DDGS, yet the gain value and IOFC responses varied depending on the marketing strategy.
Keywords: dried distillers grains with solubles; DDGS withdrawal; finishing pigs